A novel mycobacterial growth inhibition assay employing live-cell imaging of virulent M. tuberculosis and monitoring of host cell viability. (September 2020) - Andersson, Blanka; Nordvall, Michaela Jonsson; Welin, Amanda; Lerm, Maria; Schön, Thomas
Abstract: Our aim was to develop a Mycobacterium tuberculosis (Mtb) growth inhibition assay (MGIA) as a summary estimate of host immune control of virulent Mtb. Mycobacterial growth inhibition (MGI) using previously frozen human PBMCs infected with H37Rv was assessed by live-cell imaging (Incucyte©) complemented by imaging flow cytometry analysis of phagocytosis. MGI measured as relative fluorescence units (RFU) was calibrated to time to positive culture (TTP) in BACTEC 960 MGIT. At a MOI (multiplicity of infection) of 5, there was a wide range of MGI of blood donors (1.1*10 6 –2.7*10 6 RFU, n = 14). Intra- and inter-assay variability were at most 17.5 and 20.7 CV%. Cell viability at day 5 was 57 and 62% monitored by the LDH and Draq7 assays respectively. There was a strong correlation between a readout for Mtb growth using CFU counts or TTP compared to RFU (r2≥0.96). Our MGIA enabling live-cell imaging and monitoring of cell viability was able to detect a wide range of Mtb growth inhibition by PBMCs and was calibrated to several readout options for bacterial growth. This MGIA may be valuable as a surrogate marker of host immunity in a personalized medicine approach.